PEMBUATAN E-LKPD BERBASIS PENDEKATAN SAINTIFIK PADA MATERI PENGUKURAN DALAM KERJA ILMIAH FASE E SMA/MA - Hayati, Silvina; Yurnetti, Yurnetti; Desnita, Desnita; Suherman, Dea Stivani (Jurnal MIPA dan Pembelajarannya, 2025)
In the independent curriculum, teaching materials are needed that can implement the curriculum dimensions, one of which is by using LKPD. The lack of references in preparing LKPD that are in accordance with the independent curriculum for grade X Phase E and most students have difficulty understanding physics material, especially measurement. The solution provided is the creation of E-LKPD based on a scientific approach. The purpose of this study is to produce an E-LKPD based on a scientific approach on measurement material in Phase E SMA/MA scientific work that is valid and practical. The type of research used is Research and Development (R&D) using the ADDIE model. The results of the data analysis produced two research findings. First, the validation result of the E-LKPD based on a scientific approach is 89.7 in the very valid category. Second, the practicality results of the E-LKPD based on a scientific approach by teachers and students, respectively, with a value of 98 and 85.8 in the very practical category. The conclusion is that the E-LKPD based on a scientific approach on measurement material in Phase E SMA/MA scientific work is valid and practical to use in physics learning.